Full-length sequence of KIR3DL1*01501 allele found in Sub-Saharan Africa by long-range sequencing - Yindom, L; de Silva, T; Rowland-Jones, S (2014)
Full-length KIR3DL1*01501 differing from KIR3DL1*0150201 with 10 SNPs and 2 nucleotide deletion in intron 7. © 2014 John Wiley and Sons A/S.